Experimental and Numerical Studies of Ignition Delay Time and Laminar Flame Speed of JP-10 at Elevated Temperature Conditions - Yang, Junsen; Wu, Yi; Zhang, Zhenpeng; Shang, Yanlei; Pan, Lun (Frontiers in Energy Research, 2022)
In this work, the laminar flame speeds of JP-10/air mixtures and ignition delay time of JP-10/O2/Ar mixtures have been studied over a wide range of experimental conditions using a premixed Bunsen flame and a shock tube. Laminar flame speed measurements of the JP-10/air mixture were measured at T = 360–453 K, φ = 0.7–1.3 and p = 1 atm. The ignition delay times of JP-10 with fuel mole fraction of 0.2% JP-10/2.8% O2/97% Ar were measured with a heated shock tube behind the reflected shock wave at 1183–1478 K and pressure of 3.4 atm. Numerical calculation and sensitivity analysis of the laminar flame speed and ignition delay time of JP-10 were performed by using published detailed and skeletal kinetic mechanisms. The comparison of experimental and numerical results showed that all models tend to overestimate the laminar flame speed under the studied conditions, especially under lower temperature conditions (360–423 K). A temperature dependency empirical correlation of laminar flame speed was then proposed by power law theory. The sensitivity analysis identified three important reactions [H+O2 = O+OH, C5H5+H (+M) = C5H6(+M), C3H3+C2H2 = C5H5] that determined the laminar flame speed and ignition delay time.